PERTANGGUNGJAWABAN KEJAHATAN KORPORASI DALAM PEMBAYARAN UANG PESANGON AKIBAT PEMUTUSAN HUBUNGAN KERJA - Kabes, Irianto; Multiwijaya, Vience Ratna; Suar, Aprima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Of the total 536 collective agreements related to layoffs in 2019, only 147 agreements, which is equivalent to around 27 percent, provided layoff compensation in accordance with labor regulations. On the other hand, 384 agreements, or around 73 percent, did not meet the provisions of the applicable law in terms of layoff compensation payments. This research aims to identify corporate responsibility in terms of severance pay due to layoffs., This research carried out using a normative and descriptive approach, using secondary data for qualitative analysis. Deductive logic methods are applied to reach conclusions. with the problem formulation, what is the responsibility for corporate crime in the payment of severance pay due to termination of employment? Research results show that Termination of Employment (PHK) is a termination of the employment relationship between a company and employees which can occur for various reasons, including the employer's initiative, the wishes of workers, legal regulations, or decisions of the Industrial Relations Court (PHI). Layoffs require employers to provide compensation in the form of severance pay, gratuity pay, and compensation for rights in accordance with the provisions. Types of layoffs include changes in company status, efficiency, liquidation, force majeure, bankruptcy, violation of provisions, retirement, and death or permanent disability. Corporations that do not fulfill their severance pay obligations can be subject to criminal sanctions according to various theories of corporate responsibility including strict liability, vicarious liability, direct corporate criminal liability, aggregation theory, and corporate culture model.Keywords: Corporations, Employment, Crime